2015
DOI: 10.1177/1071100715619678
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Intramedullary Screw Versus Low-Profile Plate Fixation of a Jones Fracture

Abstract: Although low-profile "hook" plates offer an alternative for fixation of fifth metatarsal Jones fractures, intramedullary screw fixation may provide better resistance to bending and initiation of fracture site rotation. The influence of these mechanical characteristics on fracture healing is unknown, and further clinical investigation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Several studies evaluated different fixation methods for surgical Jones fracture treatment in various biomechanical test setups. 2,5,8,12,[14][15][16][17][25][26][27]31,[38][39][40][41] Recent attention has been focused on Jones fracture-specific implants such as specifically designed screws and plates. 2,4,16,20,31,32,40,41 Latest biomechanical studies revealed contradictory results comparing Jones fracturespecific screw to plate fixation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies evaluated different fixation methods for surgical Jones fracture treatment in various biomechanical test setups. 2,5,8,12,[14][15][16][17][25][26][27]31,[38][39][40][41] Recent attention has been focused on Jones fracture-specific implants such as specifically designed screws and plates. 2,4,16,20,31,32,40,41 Latest biomechanical studies revealed contradictory results comparing Jones fracturespecific screw to plate fixation.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,8,12,[14][15][16][17][25][26][27]31,[38][39][40][41] Recent attention has been focused on Jones fracture-specific implants such as specifically designed screws and plates. 2,4,16,20,31,32,40,41 Latest biomechanical studies revealed contradictory results comparing Jones fracturespecific screw to plate fixation. 8,10,14,16,17,[23][24][25][26][27][28]40,41 The comparison of two intramedullary screw constructs was technically more appealing to us because the clinical use of percutaneous screw placement is generally accepted as gold standard treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using simulated cadaveric Jones fractures, Huh et al compared intramedullary screws with the low profile plate. Biomechanically, the intramedullary screw resulted in greater bending stiffness, less fracture site angulation, and greater initial torsional stiffness compared to the hook plate [29].…”
Section: Discussionmentioning
confidence: 97%
“…The main finding of this study is the efficacity of the fixation using a LCP distal ulna hook plate for a novel approach. There were only 4 studies studied the plate in the treatment of FMBFs [ 13 , 15 17 ]. Three studies had evaluated the results of surgical treatment of zones I and II FMBFs using a mini-hook plate [ 13 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%